WWP1 knockout in mice exacerbates obesity‐related phenotypes in white adipose tissue but improves whole‐body glucose metabolism. Issue 3 (3rd February 2020) - Hoshino, Shunsuke; Kobayashi, Masaki; Tagawa, Ryoma; Konno, Ryutaro; Abe, Takuro; Furuya, Kazuhiro; Miura, Kumi; Wakasawa, Hiroki; Okita, Naoyuki; Sudo, Yuka; Mizunoe, Yuhei; Nakagawa, Yoshimi; et al.
Abstract : White adipose tissue (WAT) is important for maintenance of homeostasis, because it stores energy and secretes adipokines. The WAT of obese people demonstrates mitochondrial dysfunction, accompanied by oxidative stress, which leads to insulin resistance. WW domain‐containing E3 ubiquitin protein ligase 1 (WWP1) is a member of the HECT‐type E3 family of ubiquitin ligases and is associated with several diseases. Recently, we demonstrated that WWP1 is induced specifically in the WAT of obese mice, where it protects against oxidative stress. Here, we investigated the function of WWP1 in WAT of obese mice by analyzing the phenotype of Wwp1 knockout (KO) mice fed a high‐fat diet. The levels of oxidative stress markers were higher in obese WAT from Wwp1 KO mice. Moreover, Wwp1 KO mice had lower activity of citrate synthase, a mitochondrial enzyme. We also measured AKT phosphorylation in obese WAT and found lower levels in Wwp1 KO mice. However, plasma insulin level was low and glucose level was unchanged in obese Wwp1 KO mice. Moreover, both glucose tolerance test and insulin tolerance test were improved in obese Wwp1 KO mice. These findings indicate that WWP1 participates in the antioxidative response and mitochondrial function in WAT, but knockdown of WWP1 improves whole‐body glucose metabolism. Abstract : WWP1 knockout mice fed high‐fat diet have suppressed mitochondrial enzymatic activity and exacerbated oxidative stress in white adipose tissue, but decreased blood insulin levels and enhanced insulin sensitivity, resulting in improved glucose metabolism in whole body.